Hambatan Kebijakan Politik Pemerintah dan Ekonomi Masyarakat Aceh Utara Tahun 2021-2022 - Zulham; Maksalmina (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2023)
The paper is to find out and explain the obstacles of political and economic policies in the form of The Village Owned Enterprise (what so called BUMDes) has developed three types of business units, namely a land pawning, a sound system rental and a cattle breeding business units. The research approach is used a qualitative method. This research was conducted using observation and interview techniques using a list of questions as a research instrument, then the data were analyzed descriptively. The theories used are decision and politics. The obstacles that occur in government and community policies include political obstacles, economy obstacle.